2021
DOI: 10.1093/mnras/stab1340
|View full text |Cite
|
Sign up to set email alerts
|

The NIRVANDELS Survey: a robust detection of α-enhancement in star-forming galaxies at z ≃ 3.4

Abstract: We present results from the NIRVANDELS survey on the gas-phase metallicity (Zg, tracing O/H) and stellar metallicity (Z⋆, tracing Fe/H) of 33 star-forming galaxies at redshifts 2.95 < z < 3.80. Based on a combined analysis of deep optical and near-IR spectra, tracing the rest-frame far-ultraviolet (FUV; 1200–2000 Å) and rest-frame optical (3400–5500 Å) respectively, we present the first simultaneous determination of the stellar and gas-phase mass-metallicity relationships (MZRs) at z ≃ 3.4. In bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 103 publications
(187 reference statements)
10
34
1
Order By: Relevance
“…Likewise, there is no statistically significant anti-correlation between [O/Fe] and M * for the subset of galaxies in Figure 12 (Spearman ρ = −0.29, p = 0.02). Perhaps the most direct comparison of this finding to other samples is with the recent results for z ∼ 3 galaxies from Cullen et al (2021), who compared their rest-UV-measured Fe/H with the strong-line-based O-MZR from Sanders et al (2021). As we do, the authors found virtually identicalalbeit much steeper-slopes for their gas-phase metal-licity relation (O-MZR) and stellar metallicity relation (Fe-MZR).…”
Section: Astrophysical Insight From Abundance Patternssupporting
confidence: 81%
See 3 more Smart Citations
“…Likewise, there is no statistically significant anti-correlation between [O/Fe] and M * for the subset of galaxies in Figure 12 (Spearman ρ = −0.29, p = 0.02). Perhaps the most direct comparison of this finding to other samples is with the recent results for z ∼ 3 galaxies from Cullen et al (2021), who compared their rest-UV-measured Fe/H with the strong-line-based O-MZR from Sanders et al (2021). As we do, the authors found virtually identicalalbeit much steeper-slopes for their gas-phase metal-licity relation (O-MZR) and stellar metallicity relation (Fe-MZR).…”
Section: Astrophysical Insight From Abundance Patternssupporting
confidence: 81%
“…As with the O-MZR, the Fe-MZR in Figure 10 is shallower than other recent studies at z 2 (Cullen et al 2019(Cullen et al , 2021, which found β Fe/H ∼ 0.3 using galaxies' rest-UV spectra to estimate stellar metallicity. Theios et al (2019) also showed a somewhat steeper increase in stellar metallicity as a function of M * (β Fe/H ≈ 0.29) Figure 10.…”
Section: The Fe-mzrsupporting
confidence: 48%
See 2 more Smart Citations
“…Recent studies indeed find evidence for supersolar O/Fe 2 (O/Fe)| in the ISM of z ∼ 2 star-forming galaxies (e.g. Steidel et al 2016;Topping et al 2020;Cullen et al 2021). Consequently, oxygen (or, more generally, α-element)-enhanced abundance ratios are also found in local stars that formed at earlier cosmic epochs (e.g.…”
Section: Note On the Low Metallicity Thresholdmentioning
confidence: 95%